P79 Comparison of CF and Non CF LCI results using the Exhalyzer D and InnocorTM devices. (12th November 2015) - Bayfield, KJ; Saunders, C; Alton, EWFW; Davies, JC
Abstract : Background: Multiple breath washout (MBW) is a pulmonary function test that allows measurement of lung clearance index (LCI), a marker of ventilation heterogeneity. LCI is increasingly being considered as a clinical trial outcome measure. The Exhalyzer D N2 washout (N2 /ExD, Ecomedics AG, Switzerland) is the recommended technique by the ECFS CTN. Mostly our group's experience with LCI uses the Innocor TM gas analyser (Innovision, Denmark), SF6 as a tracer gas (SF6 /Inn). To understand the N2 /ExD technique, the aims of this study were to compare a) intra-test variability; b) LCI values c) LCI and FEV1 for the two techniques. Methods: 21 CF (14F, mean 20 ± 12 yrs) and 10 non-CF (8F, mean 28 ± 10 yrs) have completed MBW trials with the 2 techniques in random order on the same visit; methods previously described (Horsley et al . 2009, Jensen et al . 2013). Results: Intra-test CoV (2–3 repeats) was similar for SF6 /Inn and N2 /ExD (3.57 vs 3.78 CF, ns). LCI was significantly higher with N2 /ExD than with SF6 /Inn in both CF (14.05 vs 9.33; p = <0.0001) and non-CF (7.08 vs 6.64, p = 0.04). Both techniques show a significant correlation for LCI and FEV1 %, although the regression slopes were significantly different (p = 0.005); much steeper for N2 /ExD. Conclusions: LCI values cannot be used interchangeably between the Innocor TM and Exhalyzer D. In non CF, there was a statistically significant difference, with higher values in the N2 /ExD. The difference was much greater in CF and increased as LCI did. In the context of similar intra-test variability, the hypothesis that this may translate into improved power in future clinical trials needs to be tested. Sponsored by a non-restricted grant from Novartis. References: 1 Horsley AR, Gustafsson PM, Macleod KA. et al. Lung clearance index is a sensitive, repeatable and practical measure of airways disease in adults with cystic fibrosis. Thorax . 2008;63 :135–40 2 Jensen R, Stanojevic S, Gibney K, et al. Multiple breath nitrogen washout: a feasible alternative to mass spectrometry. PLoS One . 2013;8 :e56868